Develop growth strategies for PACE Communications Limited - Yang, Shan Yu; Tyll, Ladislav; Srivastava, Mohit; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2020)
Answer the following three questions:i. What are the relevant factors to grow the business?ii. How can PACE grow further in Kenya?iii. What are the determinants of a successful internationalization process?
Vedoucí práce: Ladislav Tyll
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2020
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2020
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses